Proper Hand Washing for Caregivers - Amy Simonne (EDIS)
Hand washing is an important way to reduce the fecal-oral transfer of germs that cause diseases. Young children and frail elders have less ability to fight germs than others. As a caregiver you can help reduce the risk of diseases that can be transmitted in a crowded environment by using proper hand washing procedures. This document is FCS 8782-Eng, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date November 2005.